Pengaruh Metode Bercerita Terhadap Kemampuan Mengungkapkan Bahasa Anak Usia 5-6 Tahun di TK Pertiwi 1 Banjarsari - Gana Kartinika Hadi (Universitas Trunojoyo Madura, 2018)
The purpose of this study is to reveal the influence of storytelling method toward the ability of revealed language the of Child Aged 5-6 Years Old at Pertiwi 1 Banjarsari. This research uses quantitative approach by using experiment method; the research design uses Pre-Experimental design (nondesign) which includes pre-test and pos-test. Subject of this research is a child aged 5-6 years old in Pertiwi 1 Banjarsari Kindergarten about 19 students. Data collecting technique through the observation and documentation. Data analysis technique the inferensial statistics by using t data experiment analysis (T-Test). The result of data analysis is acquired value r = 0,68, wich are -2,450 -11,66, thus is accepted wich means there is significanct influence between Sorytelling Method to child’s revealed language ability.